GEOCHEMISTRY OF WATER-SOLUBLE SALTS IN IRRIGATED SOILS (Scientific journal of the Fergana State University, 2025)
The article presents the results of the analysis of the water extract (1:5) of the genetic horizons of irrigated meadow sasa soils. According to the amount of dry residue, these soils are moderately and strongly saline. Hypothetical salts were calculated according to the amount of water-soluble anions and cations. It has been proven that sulfate salts predominate in irrigated meadow sasa soils and that the salinization of the latter is affected by mineralized groundwater with a sasa regime.